GRP-006 A Policy Review of the Application of the Integrated Medicines Management Service Model in Northern Ireland. (12th March 2013) - Harrison, C; Timoney, M; Scott, MG
Abstract : Background: Since 2002, the Integrated Medicines Management Service (IMM) has strategically re-engineered clinical pharmacy services in the five acute Health and Social Care Trusts (HSCTs) in Northern Ireland. The Department of Health, Social Services and Public Safety (DHSSPS) supported the initial development of the IMM informed by evidence which demonstrated improvements in patient care and efficiencies [1, 2]. These included reduced length of stay, readmission rates and drug costs with improved medicines appropriateness and communication with primary care. Against a background of the review of public administration, focus on efficiencies and future models for integrated health and social care, IMM remains a key policy initiative. Purpose: Within this context, a review of IMM service provision is being undertaken to assess the current application of the IMM model and its strategic alignment with plans for integrated health and social care. Materials and Methods: The first stage of the review involved a quantitative assessment of IMM practise within HSCTs to measure the application of the IMM model against a range of good practise indicators, relating to: use of funding for a dedicated IMM workforce; relevant staff roles and professional focus; workforce deployment across HSCT sites; availability and level of IMM service provision. Results: During 2011/12 66% of the total funding identified for IMM services in all HSCTs in Northern Ireland was used to employ pharmacists and 34% for pharmacy technicians. Within this workforce 96% of pharmacists and 98% of technicians had IMM roles included in their job descriptions with pharmacists spending 80% of their working time on clinical or IMM duties and pharmacy technicians 65%. The IMM workforce was deployed at 74% of HSCT sites (n = 17) with IMM services available for a range of bed types from Monday to Friday between 8am and 6pm. 40% of the total number of beds identified as suitable for IMM service provision across all HSCTs were reported as having active service provision during 2011/12 with activity levels ranging from 20% to 95% between HSCTs. Conclusions: IMM is regarded as a cornerstone of medicines policy in Northern Ireland and results indicate that the funding allocated for this service is being used to support the deployment of a cohort of pharmacists and pharmacy technicians with roles that are focused on clinical practise and medicines management. Results show the provision of IMM services within defined periods across HSCT sites in a range of bed types but with some variation in the active application of the IMM model between HSCTs. References: Burnett KM, Scott MG, Fleming GF, Clark CM, McElnay JC (2009), Effects of an integrated medicines management programme on medication appropriateness in hospitalised patients. Scullin C. Scott MG, Hogg A, McElnay JC, (2007), An innovative approach to integrated medicines management. No conflict of interest.